Incidence and risk factors of depressive symptoms in the highest age groups and competing mortality risk: evidence from the AgeCoDe-AqeQualiDe prospective cohort study - Maier, Alexander; Durrant-Finn, Cornelius; Pabst, Alexander; Löbner, Margrit; Eisele, Marion; Brettschneider, Christian; Heser, Kathrin; Kleineidam, Luca; Weyerer, Siegfried; Werle, Jochen; Pentzek, Michael; Fuchs, Angela; et al. (Journal of affective disorders, 2022)
Introduction - Only a few studies have investigated incidence and risk factors of depression in the highest age groups. This study aims to determine incidence rates as well as risk factors of incident depressive symptoms in latest life, adjusting for the competing event of mortality. - Methods - Data of a prospective, longitudinal, multi-centered cohort study conducted in primary care - the AgeCoDe-/AgeQualiDe study. 2436 GP patients aged 75+ years were assessed from baseline to sixth follow-up every 18 months and from seventh to ninth follow-up every 10 months. Depressive symptoms were assessed using the 15-item version of the Geriatric Depression Scale (cut-off ≥6). Competing risk regression models were used to assess determinants of incident depressive symptoms, taking care of accumulated mortality. - Results - The incidence of depressive symptoms was 39 per 1000 person-years (95% CI 36-42; last observed exit 13.26 person-years at risk). In a competing risk regression model, female sex, unmarried family status, subjective cognitive decline as well as vision and mobility impairment were significant risk factors of incident depression. - Limitations - Excluding individuals with a lack of ability to provide informed consent at baseline may have influenced the incidence of depression. Depressive symptoms were not assessed by DSM criteria. Furthermore, in studies with voluntary participation, participation bias can never be completely avoided. - Conclusion - Findings provide a better understanding of risk and protective factors of depressive symptoms in the oldest age taking mortality as a competing event into account. Addressing this aspect in future research may yield new insights in that research field.
Online verfügbar: 20 April 2022, Artikelversion: 25 April 2022
Gesehen am 05.12.2023